THE EFFECT OF BOARD OF COMMISSIONERS SIZE, INDEPENDENT COMMISSIONERS SIZE AND BOARD OF DIRECTORS SIZE ON FINANCIAL PERFORMANCE - Putri, Arina; Bakry, Mohammad Iqbal; Mustamin, Mustamin; Tanra, Andi Ainil Mufidah (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
This study aims to analyze the influence of the size of the board of commissioners, independent commissioners, and board of directors on the financial performance of manufacturing companies in Indonesia. The research approach is quantitative, using multiple linear regression analysis and secondary data. The study population includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period, with a final sample of 17 companies that met the criteria, selected using purposive sampling. The results show that simultaneously, the size of the board of commissioners, independent commissioners, and board of directors significantly influence financial performance. Partially, the size of the board of commissioners has a negative and significant effect, independent commissioners have a positive but insignificant effect, while the size of the board of directors has a positive and significant effect. The coefficient of determination indicates that variations in financial performance are explained by these three variables, while the remainder is influenced by other factors. These findings confirm that effective corporate governance management, particularly through optimizing the role of the board of directors and improving the quality of independent commissioners, can support a company's financial performance. Keywords: Size of the Board of Commissioners, Independent Commissioners, Size of the Board of Directors, Financial Performance, Corporate Governance